Analisis Pengakuan, Pengukuran dan Pengungkapan Imbalan Pasca Kerja Berdasarkan PSAK No. 24 (revisi 2013) dan Dampak Perubahannya terhadap Laporan Keuangan Pada Perusahaan Yang Terdaftar Dalam Bursa efek Indonesia - Fadillah, Dilla Nurul; Triandi, Triandi (Institut Bisnis dan Informatika Kesatuan, 2019)
Every established company certainly hopes that the company can grow rapidly, advance and have a long life. The survival of a company depends very much on what the company produces through the performance of the workers in the company. A worker will give a maximum performance if they get satisfaction from the results of their work. The satisfaction of these workers can be given through employee benefits that are appropriate for their work. With employee benefits, workers will provide maximum and good performance and have a sense of loyalty to the company. The purpose of this study was to find out how the application of PSAK No.24 (revised 2013) regarding post-employment benefits in a company, the suitability of recognition, measurement and disclosure and the impact of the application of PSAK No. 24 (Revised 2013). The author conducted research at PT. Indonesian Telecommunications.Tbk and PT. Blue Bird.Tbk. The results of the study show that the two companies have implemented post-employment benefits in accordance with PSAK No.24 (revised 2013). PT Telekomunikasi Indonesia.TbK implements both post-employment benefits programs, namely defined benefits and definite contributions, while for PT. Bird Bird.Tbk only implements a defined contribution program. Because both companies have implemented PSAK No. 24 (Revised 2013) which took effect on January 1, 2015 then the financial statements of the two companies must be reviewed. Therefore, both companies should maintain their consistency in implementing PSAK No.24 in accordance with the applicable regulations. Because employee benefits are a large operating expenses of the company and can affect the company's profit.